PENINGKATAN KETERAMPILAN MENULIS TEKS DESKRIPSI MELALUI PENERAPAN STRATEGI THINK TALK WRITE (TTW) PADA MURID KELAS III SDN 16 AIR TAWAR TIMUR KOTA PADANG - Mulniati, Winda; Chandra (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research is motivated by the low descriptive text writing skills of third-grade students of SDN 16 Air Tawar Timur, Padang City, which is caused by teacher-centered learning, lack of active student participation, and less than optimal implementation of writing stages. This research aims to improve descriptive text writing skills through the implementation of the Think Talk Write (TTW) learning strategy. The method used is Classroom Action Research (CAR) with a qualitative and quantitative approach implemented in two cycles, where each cycle includes the planning, implementation, observation, and reflection stages. Data collection techniques are carried out through observation, tests, and non-tests with research subjects including class teachers as observers, researchers as practitioners, and third-grade students as participants. The results of the study showed an increase in various aspects, namely the RPPM assessment which increased from 80% (good) in cycle I to 100% (very good) in cycle II, the teacher aspect assessment increased from 75% (sufficient) to 100% (very good), and the student aspect assessment increased from 75% (sufficient) to 100% (very good). In addition, the average narrative text writing skills of students also increased from 63.15% (needs guidance) in cycle I to 95.11% (very good) in cycle II, so it can be concluded that the application of the Think Talk Write (TTW) learning strategy is effective in improving the descriptive text writing skills of grade III students of SDN 16 Air Tawar Timur, Padang City.